PENDETEKSIAN PLAT NOMOR KENDARAAN MENGGUNAKAN ALGORITMA YOU ONLY LOOK ONCE V3 DAN TESSERACT - Muhamad Rizky Fauzan; Ari Purno Wahyu Wibowo (Jurnal Ilmiah Teknologi Infomasi Terapan, 2021)
The development of technology is currently growing very rapidly. One technology that is currently being developed on a large scale is Artificial Intelligence. Artificial Intelligence or AI has various functions and purposes depending on the system created. One of them is to detect objects and text from images or videos. An example of the application of this technology is the detection of objects and text on vehicle number plates. In this study, a system design was carried out using the You Only Look Once V3 algorithm as an object detection algorithm and Tesseract Optical Character Recognition as a text in image detector. This design is assisted by the OpenCV library in the python programming language and uses an image dataset that is already available. This study aims to determine the level of accuracy of the You Only Look Once V3 algorithm combined with Tesseract Optical Character Recognition.